ИИВ олий таълим тизими курсантларида ўқув мотивация: муаммо ва ечимлар - Тургунов, Н.Ш (SCIENCE and SOCIETY, 2024)
This article the cadets of the higher education system of the Ministry of Internal Affairs expressed their opinions on
Keywords: educational motivation; learning; activity; external and internal motives; motivating action; educational process; social; professional success